The affected factors of puberty and menstrual disturbances among female students at Al-Andalus university - Salman, Safa K.; Mohammad, Marah H.; Mhanna, Aya Y.; Saleh, Safaa Y. (International Journal of Scientific Reports, 2020)
Background: The aim of the study was to determine the pubertal, menarcheal age and menstrual disturbances, and the factors affecting them, during the war in Syria, among AL-Andalus university female students. Methods: A self-reported questionnaire was answered from 156 students. The questions were about socio-demographic information, reproductive and menstrual patterns, and the participants’ lifestyle. Inclusion criteria included girls 17 to 25 years old, no systemic diseases and completed the questionnaire. The questionnaire was answered in the university. The researchers clarified the aim of the study and got the voluntary consent. The data of 148 girls were entered intoSPSS. Exclusion criteria excluded girls (≤17 and ≥25) years and those who did not complete the questionnaire. The study was conducted from 20 January 2020 to 20 March 2020. Results: 148 cases were analyzed. The mean age of puberty and menarche of our students are 12.38±1.41 and 13.38±1.35 years respectively. Fast food and changing adopted place have a significant association with menstrual disturbances (p<0.05). Blood group, faculty, weight and the mother’s menarcheal age have no effects on them (p>0.05). Conclusions: Not found any change in the age of puberty and menarche, but this does not prevent to make more studies in different places in Syria in the future.